2019
DOI: 10.1002/hpm.2768
|View full text |Cite
|
Sign up to set email alerts
|

District‐level impacts of health system decentralization in Indonesia: A systematic review

Abstract: Summary The local‐level impacts of decentralizing national health systems are significant yet infrequently examined. This review aims to assess whether localized health services delivery in Indonesia, which commenced a health system decentralization process in 2001, achieved its objectives or could be enhanced. A systematic review was undertaken to collate published evidence regarding this topic and synthesize key findings holistically using the six building blocks framework of the World Health Organization (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 69 publications
2
43
0
Order By: Relevance
“…32 From a helicopter view, most of the components of a wellperforming dengue surveillance system were indeed already available, although not in all hospitals. In line with a recent review of the decentralized Indonesian health system, 33 our study found issues in several of the building blocks of a wellperforming health system as defined by the WHO. 34 First, it was found that the regulatory frameworks used to support the staff in diagnostics and reporting were inconsistent.…”
Section: Discussionsupporting
confidence: 87%
“…32 From a helicopter view, most of the components of a wellperforming dengue surveillance system were indeed already available, although not in all hospitals. In line with a recent review of the decentralized Indonesian health system, 33 our study found issues in several of the building blocks of a wellperforming health system as defined by the WHO. 34 First, it was found that the regulatory frameworks used to support the staff in diagnostics and reporting were inconsistent.…”
Section: Discussionsupporting
confidence: 87%
“…East Java (Trenggalek, Jombang, Ngawi, Sampang, Pamekasan) was below 51%, with the lowest level at 9% in Sampang district, East Java (12).…”
Section: Sustainability Componentsmentioning
confidence: 95%
“…During transition from a centralized to decentralized system, maternal and child immunization coverage and availability remained pressing issues at the district level in Indonesia. Complete child immunization in most districts in Indonesia was below the WHO recommendation threshold of 80% (12). In 2002, complete child immunization coverage in central java (Cilacap, Rembang, Jepara, Pemalang, Brebes) and…”
Section: Sustainability Componentsmentioning
confidence: 98%
See 2 more Smart Citations